Seasonal thermochemical energy storage: Comparison of the experimental results with the modelling of the falling film tube bundle heat and mass exchanger unit. (September 2017) - Daguenet-Frick, Xavier; Gantenbein, Paul; Müller, Jonas; Fumey, Benjamin; Weber, Robert
Abstract: This paper focuses on the assessment of a heat and mass exchanger dedicated to an absorption/desorption seasonal thermal energy storage system. The closed sorption heat storage based on water vapour absorption in aqueous sodium hydroxide (NaOH-H2 O) solution theoretically achieves a significantly higher volumetric energy density compared to conventional hot water storage systems. To this purpose, a prototype designed for a power output of 10 kW was built and operated in both absorption and desorption mode under steady state boundary conditions. In this work, the influence of two main parameters on the exchanged power is evidenced. Furthermore, a comparison with the results of the initial numerical model used to design the heat and mass exchanger is carried out. On one hand it is found that, for the absorption process, the measured exchanged power is much lower than the numerically predicted value. On the other hand, for the desorption process the numerical and experimental results have the same order of magnitude. Physical explications of the strongly diverging results encountered during the absorption process as well as an improved heat transfer coefficient model for the desorption process are proposed. Graphical abstract: Highlights: Assessment of an aqueous sodium hydroxide seasonal thermal energy storage prototype. Prototype heat and mass transfer zone run in absorption and desorption mode under steady state boundary conditions. Experimental results comparison with the numerical model. Thermo-physical explications proposed for the strongly diverging absorption results. Proposal of an improved heat transfer coefficient model for the desorption process.